2011
DOI: 10.1111/j.1524-4725.2011.01880.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Surgical Methods (Winograd and Sleeve Method) in the Treatment of Ingrown Toenail

Abstract: The sleeve method seems to be more practical and appropriate for patients planning to go back to work sooner and better fulfills the main characteristics for the primary treatment of choice. The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 9 publications
1
28
0
2
Order By: Relevance
“…Also, it requires longer periods for sick leave and has a greater incidence of recurrence (6,11). A study of 100 patients with ingrown toenails treated with the conservative guttersplint method or Winograd technique reported that although the recurrence rate was lower for the patients treated with Winograd technique, the postoperative loss of work was much longer (2 weeks with the Winograd technique and 1.1 weeks with the gutter-splint method) (19). A retrospective survey of 68 patients with an ingrown toenail treated with the Winograd technique reported a considerably high recurrence rate (13.2%) and significantly lower cosmetic ratings in the female patients (20).…”
Section: Discussionmentioning
confidence: 96%
“…Also, it requires longer periods for sick leave and has a greater incidence of recurrence (6,11). A study of 100 patients with ingrown toenails treated with the conservative guttersplint method or Winograd technique reported that although the recurrence rate was lower for the patients treated with Winograd technique, the postoperative loss of work was much longer (2 weeks with the Winograd technique and 1.1 weeks with the gutter-splint method) (19). A retrospective survey of 68 patients with an ingrown toenail treated with the Winograd technique reported a considerably high recurrence rate (13.2%) and significantly lower cosmetic ratings in the female patients (20).…”
Section: Discussionmentioning
confidence: 96%
“…1 Adolescents and young adults are affected more frequently than other age-groups. Ingrown toenail most often occurs on the big toe, although it can occur on other digits.…”
mentioning
confidence: 99%
“…One group applied ANL 2 weekly and the other group did not receive any treatment. Recurrence occurred more quickly in the untreated group and at end point, 70.8% remained cured in treated group, while 50% in the untreated group. Author concluded that ANL can serve as a good prophylactic tool to prevent recurrence of OM.…”
Section: New In Onychomycosis Treatmentmentioning
confidence: 74%
“…Payvandi et al [70] compared Winograd and sleeve methods for the treatment of ingrown toe nails in 100 patients. They found that the participants treated with sleeve method experienced shorter surgery duration, less work day loss, and the recurrence rate were similar in two groups.…”
Section: New In Onychomycosis Treatmentmentioning
confidence: 99%